Interview with Mr. Deepak Bohra Honorable Minister, Ministry of Forest & Soil Conservation, Government of Nepal (Hydro Nepal: Journal of Water, Energy and Environment, 2011)
Not available. InterviewDOI: 10.3126/hn.v6i0.4199Hydro Nepal Journal of Water, Energy and Environment Vol. 6, January 2010 Page: 78-80 Uploaded Date:  24 January, 2011